Expression analysis of opaque2, crtRB1 and shrunken2 genes during different stages of kernel development in biofortified sweet corn. (May 2022) - Baveja, Aanchal; Chhabra, Rashmi; Panda, Kusuma K.; Muthusamy, Vignesh; Mehta, Brijesh K.; Mishra, Subhra J.; Zunjare, Rajkumar U.; Hossain, Firoz
Abstract: Sweet corn is a popular food worldwide. Traditional shrunken2 ( sh2 )-derived sweet corn possesses low lysine (0.150–0.250%), tryptophan (0.030–0.040%) and provitamin-A (proA: 3–4 μg/g). Here transcript profiles of a newly developed 12 sh2 -based sweet corn inbreds possessing mutant opaque2 ( o2 ) and β-carotene hydroxylase ( crtRB1 ) genes were analyzed during three stages of kernel development viz ., 20-, 24- and 28- days after pollination (DAP). Introgressed inbreds had higher lysine (0.309%), tryptophan (0.077%) and proA (17.28 μg/g). Across stages of kernel development, transcript levels of mutant sh2, o2 and crtRB1 genes were significantly lower than the wild type ( sh2 +, o2 + and crtRB1 + ) alleles. Among genes, sh2 had the highest level of transcripts accumulation followed by crtRB1 and o2 . While o2 and crtRB1 transcripts attained peaks at 24-DAP, the highest peak for sh2 was recorded at 28-DAP. Strong negative correlation (r = −0.99 to −0.71) was observed between the transcripts and corresponding nutrients. The study provided insight of complex regulation of sh2, o2 and crtRB1 genes during various stages of kernel development. This is a first of its kind study to analyze the transcript level variation of mutant allele of sh2, o2 and crtRB1 genes among novel biofortified sweet corn genotypes. Graphical abstract: Image 1 Highlights: Introgressed inbreds possessed higher lysine, tryptophan & provitamin-A. Transcript of mutant sh2, o2 & crtRB1 had lower levels than the wild type allele. sh2 had the highest level of transcript accumulation followed by crtRB1 and o2 . o2 and crtRB1 transcripts had peak at 24-DAP & peak for sh2 was recorded at 28-DAP. Negative correlation was observed between the transcripts and respective nutrients.